TRANSFORMING LITERARRY TEXTS: A MULTILITERACIES APPROACH TO ENGAGING DIGITAL NARRATIVES - Mandarani, Vidya; Megawati, Fika (University of Kuningan, 2024)
Combining technology with literary texts may help solve the obstacles faced in modern education. Digital storytelling (DST) is an engaging approach that involves students with literature, developing creativity, cultural knowledge, and character development, while creating a dynamic classroom atmosphere. This research investigated how the lecturer use multiliteracies pedagogy to facilitate students in transforming literary text into a DST and their responses to this process. The researchers used purposive sampling and performed a qualitative case study to get detailed insights into how multiliteracies instruction transforms literary text into digital storytelling among 25 ELT students at Universitas Muhammadiyah Sidoarjo. The results showed that the DST task promotes students’ active involvement with texts. They scrutinised the components of the narrative and converted the text into a digital story. The stages of multiliteracies teaching had a good influence on students’ learning experiences, improved their comprehension of literary content, and encouraged them to combine literature and technology. Ultimately, multiliteracies teaching may transform passive learning into active engagement and foster students’ creativity, cultural proficiency, and multimodal literacy abilities.